An Analysis of The Scaffolding Process to Teach English for Young Learners in Elementary School - Achmad Nur Ilmi; Valentina Dyah Arum Sari (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
The fact that English served as the local content had given another challenge to the Elementary school students in learning English as a Foreign Language. Although, now, curriculum is in the transition into a freedom of learning Independent which English starts to be included as the subject to learn in first and fourth graders, students are still struggling in following the teaching and learning process of the subject. The right techniques must be selected and applied to help students achieve the learning goals. One promising technique to teach EYL is scaffolding. This study aimed (1) to reveal the Scaffolding process in teaching English and (2) to find out benefits of the scaffolding process in teaching English for Young Learners in one state Elementary School in Padangan, East Java. The participants were the English teacher and 15 students from fourth grade. This study applied mixed-method research. The instruments to obtain the data were observation, questionnaire, and interview. The research findings that the scaffolding process existed in the teaching and learning process of English in the elementary school. Several scaffolding strategies were applied in the teaching process of English subjects. The students’ responses towards the scaffolding reached a medium qualification which was 67%. Besides, the students’ responses on the benefits of scaffolding showed medium qualification which was 66%. Furthermore, it could be concluded that the scaffolding process were well implemented in the process of teaching English in Elementary school. Also, the existence has given positive responses to the students in learning English.